Method of hybrid revascularization of miocard in patients with atherosclerotic damage of coronary vessels - Gabrielyan, A.; Domanskyy, T.; Beregovoy, O. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Goal – to evaluate the efficacy and safety of total revascularization of cardiac muscle in patients with ischemic heart disease and multivessel coronary disease by combination of different methods of PCI and CABG. Materials and methods. The study included 26 patients that underwent total revascularization of myocardium by combination of the traditional methods of PCI and CABG OFF PUMP. All patients had myocardial infarction in past, multivessel coronary disease and had different classes of stenocardia. Results and discussion. There weren’t any complications in early postoperative period (30 days after operation). 8 patients had extended postoperative exudation. Arrhythmogenic complications such as atrial fibrillation had 4 patients. After second stage of PCI special device for femoral artery closure Angio Seal was used in all patients. Conclusions. The results of study confirm that these methods are effective and safe.